Comparison of acupuncture, moxibustion, and pharmacotherapy in improving diarrhea-predominant irritable bowel syndrome - Zhang, Peiqin; Chen, Yao; Lai, Biyu; Wang, Shuangshuang; Li, Dan; Wen, Runlin; Duan, Yaping; Liu, Dan; Li, Bo; She, Chang (Frontiers in Microbiology, 2025)
IntroductionAcupuncture, moxibustion, and pharmacotherapy are widely used for diarrhea-predominant irritable bowel syndrome (IBS-D), but their comparative efficacy and microbial mechanisms remain unclear.MethodsWe evaluated therapeutic outcomes in IBS-D rats through physiological and colonic indicators and characterized gut microbiota using 16S rDNA sequencing with network and modular analyses.ResultsAcupuncture and moxibustion more effectively normalized stool form, diarrhea index, fecal water content, and fecal pellet counts compared to pharmacotherapy, which provided partial improvement with residual symptoms such as faster colonic transit. A total of 33 microbial taxa were identified as biomarkers, with distinct profiles associated with each intervention. Specifically, acupuncture was linked to increased levels of Pseudomonas and Turicibacter, moxibustion to RF39, and pharmacotherapy to Fusobacteriota, Blautia, and Clostridium_sensu_stricto_1. Furthermore, we also found that the ratio of Firmicutes to Bacteroidetes was a key factor in IBS-D pathogenesis. Key genera such as Muribaculum were modulated by the interventions to alleviate symptoms. Acupuncture and moxibustion restructured gut microbiota networks to improve connectivity and clustering, while pharmacotherapy resulted in a more heterogeneous network with a higher number of negative correlations with physiological parameters.ConclusionThese results demonstrated that acupuncture and moxibustion achieved superior therapeutic effects through distinct remodeling of microbial networks and host–microbe associations, providing mechanistic insight into microbiota-mediated IBS-D treatment.